A Severe Case of Tuberculosis Radiologically and Endoscopically Mimicking Colorectal Cancer with Peritoneal Carcinomatosis. (3rd October 2017) - Rath, Timo; Atreya, Raja; Geißdörfer, Walter; Lang, Roland; Nägel, Andreas; Neurath, Markus F.
Abstract : Although generally rising in incidence, intestinal tuberculosis is still rare in western countries and due to unspecific manifestations mainly as ulcerations on endoscopy, diagnosis of intestinal tuberculosis is challenging. Within this report, we describe a case of severe intestinal tuberculosis radiologically and endoscopically masquerading as colorectal cancer with peritoneal carcinomatosis. Our case exemplifies that intestinal tuberculosis needs to be considered as a differential diagnosis in patients at risk and that undelayed and sensitive diagnosis of intestinal tuberculosis is of central importance for avoiding unfavorable disease outcome.